The Effects of HVDC Connection Line on Small Signal Stability in Four-Area Power System - Yildirim, Burak; Yildiz, Suleyman; Ozdemir, Mahmut Temel (Ieee, 2019)
High Voltage Direct Current (HVDC) systems which is a power electronics technology, will affect the control and stability of power systems with developments in power electronics. In this study, the effect of HVDC lines connected in parallel to High Voltage Alternating Current (HVAC) transmission lines on system stability and frequency oscillations were investigated in a four-area interconnected power system. The model of a four-area power system was created in Matlab / Simulink environment in this study. Two scenarios have been created for the study, the scenario of adding a HVDC connection between area 1 and area 2 and including the scenario of adding HVDC connection between area 1 and area 2 and between area 1 and area 3. Three different cases which are namely, only with alternating current (AC) connection, direct current (DC) connection parallel to AC lines and DC-connected state with phase-locked loop (PLL) parallel to AC lines were examined in each scenario cases. In a 4-area power system, the gains of the controllers were determined using the Optics inspired optimization (010) algorithm with Integral Squared Error (ISE) objective function. In the continuation of the study, eigenvalue analysis study was performed for 4-area power system whose controller gains were determined and eigenvalues of the models were obtained. Afterwards, relationship between eigenvalues and state variables was determined via sensitivity analysis. With the help of the analysis studies, it was tried to show the effects on the frequency oscillations and stability of the areas to which they are connected by adding HVDC connection lines with and without PLL to the power system.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: HVDC; HVAC; Load-Frequency Control; Automatic Generation Control; Eigenvalue and Sensitivity Analyze